Predicting Substance Abuse from Attention Deficit/Hyperactivity Disorder Symptoms in Adult - Jaber Alizadeh G; Mansor Bayrami; Toraj Hashemi (Drug Control Headquarters, Research and Education Office, 2013)
Objective: This study is aimed to predict substance abuse from child and adult attention deficit/hyperactivity disorder symptoms. Method: To this purpose 361 students were selected via stratified random sampling from different faculties of Tabriz University and completed Canners Adult ADHD Rating scale-self report Form & Subscale Questionnaire, Wender Utah Rating Scale, Addiction Acknowledgment Scale & Mac Andrew Alcoholism-Revised Scale. Findings: To analyze the data Pearson correlation and multiple regressions (step by step) were used. Results indicated that there is significant relation between addiction acknowledgment and alcoholism via child and adult attention deficit hyperactivity disorder symptoms. Also, results indicated that child and adult attention deficit hyperactivity disorder symptoms predicted addiction acknowledgment and alcoholism. Conclusion: According to this results these can be explained that behavioral disorders, especially ADHD have effect in tendency to drug and therefore primary treatments of behavioral disorders can prevent drug abuse.